2002
DOI: 10.1088/0305-4470/35/20/101
|View full text |Cite
|
Sign up to set email alerts
|

Curved planar quantum wires with Dirichlet and Neumann boundary conditions

Abstract: We investigate the discrete spectrum of the Hamiltonian describing a quantum particle living in the two-dimensional curved strip. We impose the Dirichlet and Neumann boundary condition on opposite sides of the strip. The existence of the discrete eigenvalue below the essential spectrum threshold depends on the sign of the total bending angle for the asymptotically straight strips.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 7 publications
3
51
0
1
Order By: Relevance
“…Our main result is a lower bound to the spectral threshold of the Laplacian in a (bounded or unbounded) Dirichlet-Robin strip. This enables us to prove quite easily non-existence results about the discrete spectrum for certain waveguides, and generalize in this way the results of Dittrich and Kříž [9]. Moreover, we show that certain combinations of boundary conditions and geometry lead to Hardy-type inequalities for the Laplacian in unbounded strips.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our main result is a lower bound to the spectral threshold of the Laplacian in a (bounded or unbounded) Dirichlet-Robin strip. This enables us to prove quite easily non-existence results about the discrete spectrum for certain waveguides, and generalize in this way the results of Dittrich and Kříž [9]. Moreover, we show that certain combinations of boundary conditions and geometry lead to Hardy-type inequalities for the Laplacian in unbounded strips.…”
Section: Introductionsupporting
confidence: 71%
“…We refer to [27,28] for the former and to [9,30,25] for the latter. Moreover, these types of boundary conditions are relevant to other physical systems (cf [13,8,21]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides an insight into the mechanism which is behind the qualitative results obtained by Dittrich and Kříž in their 2002 letter [5]. Using −Δ Ωε DN as a model for the Hamiltonian of a quantum waveguide, they show that the discrete eigenvalues exist if, and only if, the reference curve γ of sign-definite κ is curved "in the right direction", namely if the Neumann boundary condition is imposed on the "locally longer" boundary (i.e.…”
Section: Introductionmentioning
confidence: 61%
“…Dittrich and Kříž [7] demonstrated that the discrete spectrum of the Laplacian in any asymptotically straight planar strip is empty provided the curvature of the boundary curves does not change sign and the Dirichlet condition on the locally shorter boundary is replaced by the Neumann one. A different proof of this result and an extension to Robin boundary conditions were performed in [14].…”
Section: Introductionmentioning
confidence: 99%